Antiprotozoal activity of natural products from Nigerien plants used in folk medicine - Sevik Kilicaslan, Ozlem; Cretton, Sylvian; Hausmann, Estelle; Quirós-Guerrero, Luis; Karimou, Soumana; Kaiser, Marcel; Mäser, Pascal; Christen, Philippe; Cuendet, Muriel (Frontiers in Pharmacology, 2023)
In the course of the screening of plants from Niger for antiprotozoal activity, the methanol extract of Cassia sieberiana, and the dichloromethane extracts of Ziziphus mauritiana and Sesamun alatum were found to be active against protozoan parasites, namely Trypanosoma brucei rhodesiense, Trypanosoma cruzi, Leishmania donovani and/or Plasmodium falciparum. Myricitrin (1), quercitrin (2) and 1-palmitoyl-lysolecithin (3) were isolated from C. sieberiana. From Z. mauritiana, the three triterpene derivatives 13, 15 and 16 are described here for the first time. Their chemical structures were determined by 1D and 2D NMR experiments, UV, IR and HRESIMS data. The absolute configurations were assigned via comparison of the experimental and calculated ECD spectra. In addition, eight known cyclopeptide alkaloids (4, 5, 7-12), and five known triterpenoids (6, 14, 17-19) were isolated. The antiprotozoal activity of the isolated compounds, as well as of eleven quinone derivatives (20-30) previously isolated from S. alatum was determined in vitro. The cytotoxicity in L6 rat myoblast cells was also evaluated. Compound 18 showed the highest antiplasmodial activity (IC50 = 0.2 µM) and compound 24 inhibited T. b. rhodesiense with an IC50 value of 0.007 µM. However, it also displayed significant cytotoxicity in L6 cells (IC50 = 0.4 µM).